Youth’s perception toward ecotourism as a possible model for sustainable use of local tourism resources - Stanciu, Mirela; Popescu, Agatha; Sava, Camelia; Moise, George; Nistoreanu, Bogdan Gabriel; Rodzik, Jarosław; Bratu, Iulian Alexandru (Frontiers in Environmental Science, 2022)
The knowledge, perception, and behavior of young people towards ecotourism are important for the sustainable development of this sector. The purpose of the research is to evaluate and analyze the knowledge of young Romanian students about ecotourism and the main ecotourism destinations in Romania, their behavior in relation to the practice of this form of sustainable tourism at the local level in the last two years (2020 and 2021), and the people's use of the Internet for planning holidays and digital applications while traveling in nature. Quantitative research was conducted based on a self-administered questionnaire, structured in 13 sections on ecotourism, to which were added the socio-demographic data of the respondents. The conclusions of the research are that young people know well the main ecotourism destinations in Romania, they choose them according to the beauty of the landscape, the multitude of outdoor activities and the hospitality of the hosts. In the last two years of the pandemic, young people have visited several times the main existing eco-tourism destinations locally, with an average vacation duration of 1-3 days. The Internet remains the main source of information, and in the field, they use mobile applications that allow the download of digital maps and recognize different plant species. By integrating various activities in nature, in close connection with the local culture, ecotourism can contribute to the sustainable use of local tourism resources. The paper provides a detailed and realistic picture of the knowledge and the type of ecotourism experience that young people want. The implications are theoretical and managerial, highlighting the importance of assessing the preferences of young ecotourists, as a basis for developing ecotourism strategies, sustainable use of local tourism resources, and management of protected areas.